STUDI BANDING KUAT TARIK ANGKUR PADA ANGKUR CAST-IN DAN POST INSTALLED - Christianto, Daniel; Liucius, Yenny Untari; Leman, Sunarjo; Kholin, Davin; Zorovian, Nelson (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
Anchors are connecting devices used to attach and install structural concrete components to other components. There are two types of anchor installation methods, cast-in and post installed systems. Cast-in anchors have advantages in terms of behavior and failure modes that are more predictable, while post-installed anchors are more commonly used due to its cost-effectiveness. One type of post-installed anchor is the adhesive anchor. Adhesive anchors are installed by inserting reinforcing bars into drilled holes in concrete that have been injected with adhesive. However, despite the various advantages and disadvantages of each anchor installation method, there are differences in anchor behavior and pull-out capacity that needs to be known. This research conducted pull-out tests with a confined test method on both cast-in anchors and adhesive post installed anchors installed with HILTI HIT-RE 500V3 chemical adhesive, using anchor rebars with diameters of 13mm and 16mm with an embedment depth of 5D on all samples. From the results, the pull-out capacity ratio of post installed/cast-in anchors for D13 anchors is 1,25 at the edge and 1,03 at the center. For D16 anchors, the values obtained are 1,20 at the edge and 1,34 at the center. Abstrak Angkur merupakan alat penghubung yang digunakan untuk menghubungkan dan memasang komponen struktur beton pada komponen lainnya. Terdapat dua jenis pemasangan angkur yaitu sistem pemasangan cast-in (cor di tempat) dan post installed (pasca pasang). Angkur cor di tempat memiliki kelebihan pada perilaku dan mode kegagalan yang lebih dapat diprediksi, sementara pemasangan pasca pasang lebih banyak digunakan karena merupakan cara yang cukup ekonomis. Salah satu jenis angkur pasca pasang adalah angkur pasca pasang adhesif. Angkur pasca pasang adhesif merupakan jenis angkur yang dipasang dengan memasukkan batang tulangan ke dalam lubang bor pada beton yang telah ditambahkan dengan adhesif. Namun dengan berbagai kelebihan dan kekurangan masing-masing cara pemasangan angkur, masih terdapat perbedaan dalam perilaku angkur dan kapasitas tarik angkur yang perlu diketahui. Pada penelitian ini dilakukan uji tarik dengan metode confined test pada angkur cor di tempat dan angkur pasca pasang adhesif yang dipasang dengan perekat adhesif HILTI HIT-RE 500V3 dengan tulangan angkur diameter 13 mm dan 16mm dan kedalaman penanaman 5D pada semua sampel. Dari hasil pengujian diperoleh perbandingan rasio kuat tarik angkur post installed/cast-in untuk angkur D13 sebesar 1,25 pada bagian tepi dan 1,03 pada bagian tengah. Untuk angkur D16 diperoleh nilai 1,20 pada bagian tepi dan 1,34 pada bagian tengah.